Particleboard properties from Mahang Gajah (Macarranga gigantea) particles / Nurrohana Ahmad, Jamaludin Kasim and Nafizah Hassan - Ahmad, Nurrohana; Kasim, Jamaludin; Hassan, Nafizah (2011)
The objective of the study was to evaluate the properties of particleboard produced from Macaranga gigantea and to study the effect of board density variation and wax content on particleboard properties. Mahang wood density was found to be in the range of 351.35 kg m-3 to 354.92 kg m-3. The result for bulk density for admxiture of trunk and branch of Mahang particles was 75.75 g/l. Particleboard with density of 650 kg/m3 gave the highest mechanical properties for both boards with 0% and 1% wax content. The MOR, MOE and IB were shown to increased with higher density. Boards with 1% wax addition showed lower mechanical properties. For physical properties, that is thickness swelling gives same trend like mechanical properties. For water absorption, the result decreases with the increase of board density. All boards failed to meet the minimum requirements of the BS EN Standards.